Enzyme‐Powered Nanobots Enhance Anticancer Drug Delivery. (27th November 2017) - Hortelão, Ana C.; Patiño, Tania; Perez‐Jiménez, Ariadna; Blanco, Àngel; Sánchez, Samuel
Abstract: The use of enzyme catalysis to power micro‐ and nanomotors exploiting biocompatible fuels has opened new ventures for biomedical applications such as the active transport and delivery of specific drugs to the site of interest. Here, urease‐powered nanomotors (nanobots) for doxorubicin (Dox) anticancer drug loading, release, and efficient delivery to cells are presented. These mesoporous silica‐based core–shell nanobots are able to self‐propel in ionic media, as confirmed by optical tracking and dynamic light scattering analysis. A four‐fold increase in drug release is achieved by nanobots after 6 h compared to their passive counterparts. Furthermore, the use of Dox‐loaded nanobots presents an enhanced anticancer efficiency toward HeLa cells, which arises from a synergistic effect of the enhanced drug release and the ammonia produced at high concentrations of urea substrate. A higher content of Dox inside HeLa cells is detected after 1, 4, 6, and 24 h incubation with active nanobots compared to passive Dox‐loaded nanoparticles. The improvement in drug delivery efficiency achieved by enzyme‐powered nanobots may hold potential toward their use in future biomedical applications such as the substrate‐triggered release of drugs in target locations. Abstract : The capability of enzyme‐propelled nanomotors to enhance drug delivery is investigated in this study. Urease‐powered nanomotors show active motion in ionic media and significantly improve the release of doxorubicin in the presence of urea. The synergy between the resulting catalytic products and the enhanced drug delivery results in higher cytotoxic effect toward HeLa cells.